Knowledge on Biomedical Waste Management among Nurses Working in a Hospital of Biratnagar - Gautam, Sapana; Mandal, Punam Kumari; Yangden, Namita; Rai , Munawatee (Tribhuvan University Journal, 2021)
Biomedical wastes (BMWs) are the waste generated within the hospital. The increasing number of hospitals in the public and private sectors has made a significant generation of hospital waste. Improper waste management has a direct impact on human health and the environment. The objective of this study is to identify the knowledge on biomedical waste management among nurses in a hospital at Biratnagar. A descriptive cross-sectional study was conducted among nurses working in Neuro Cardio and Multispecialty Hospital. The nonprobability purposive sampling technique was used to collect data from 101 nurses using a semi-structured and self-administered questionnaire. Data entry and analysis were done in Statistical Package for Social Science (SPSS) version 20. Descriptive analysis was done by using mean and standard deviation and in inferential analysis chi-square test was used to find the association between level of knowledge and selected demographic variables. The findings showed that among 101 respondents, the majority (88.1%) had a moderate level of knowledge and there were no associations between nurse’s level of knowledge on biomedical waste management and selected demographic variables. It is recommended that continuing education and time to time training classes should be conducted by hospital authorities so that knowledge among nurses on biomedical waste management can be increased.